RELATIONSHIP BETWEEN FLUENCY AND COMPREHENSION IN READING ACTIVITY: A BRIDGE TO BUILD READING PROFICIENCY - Meutia Rachmatia (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2022)
Reading activity is not only about reading in silent situation. Expert said reading aloud is some approach that can improve reading proficiency. Some researchers showed that reading fluency is a part that takes a big portion in reading aloud activity but some experts said that comprehension of the readers that takes an important part. Based on that situation, this paper focuses on discussing the overview by the experts and previous study of how reading comprehension and fluency are related. It also provides the brief how that correlation can improve reading proficiency for EFL students.